(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
The reaction of exocyclic enaminones namely, 2-(dimethylaminomethylene)-3,4-dihydro-2H-naphthalen-1-one,Â 3-(dimethylaminomethylene)-thiochroman-4-one and 2-(dimethyl-aminomethylene)-indane-1,3-dione, each with heterocyclic diazonium salts afforded the respective hydrazones which undergo either in situ dehydrative cyclization or cyclized by heating with acetic acid to give polycyclic compounds. The structure of all the newly synthesized products were confirmed by elemental and spectral (IR, IH NMR, Mass) data. Also, the biological activity of some of the prepared compounds was tested against some microorganisms and promising results were obtained.